Comparative study of the treatment of hepatic hydatidosis due to cystectomy: Hydatidectomy and total adventicectomy and conservative procedures - Torterolo, Edgardo; Perrier, José Pedro; Aizen, Bernardo; Piacenza, Guillermo; Castiglioni, Juan Carlos; Piñeyro, Alberto; Peyroulou, Alfredo; Misa, Carlos; Vergara, Mirta (Cirugía del Uruguay, 1990)
Authors present a six year long study (1980-1986) on hepatic hydatidosis treatment. The research team was divided into two groups according to treatment: one group performed cystostomies (with or without emerging adventitia resection), and the other performed cystectomies (total hydatid-adventitectomy).